2013
DOI: 10.1088/0957-4484/24/45/455705
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoribbon–PVA composite as EMI shielding material in the X band

Abstract: A very thin graphene nanoribbon/polyvinyl alcohol (GNR/PVA) composite film has been developed which is light weight and requires a very low concentration of filler to achieve electromagnetic interference (EMI) shielding as high as 60 dB in the X band. Atomic force microscope studies show very well conjugated filler concentration in the PVA matrix for varying concentrations of GNR supported by Raman spectroscopy data. The films show 14 orders of increase in conductivity with a GNR concentration of 0.75% [correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 38 publications
3
59
2
Order By: Relevance
“…Therefore, high conductivity, high permeability and sufficient thickness are the perquisites to achieve the required skin depth [10][11][12]. However, high conductivity is not the only criterion for shielding.…”
Section: Carbon Nanostructure Composite For Emi Sheildingmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, high conductivity, high permeability and sufficient thickness are the perquisites to achieve the required skin depth [10][11][12]. However, high conductivity is not the only criterion for shielding.…”
Section: Carbon Nanostructure Composite For Emi Sheildingmentioning
confidence: 99%
“…Therefore, the researchers are trying to develop a state-of-the-art and commercially viable nanocomposite which will have all such characteristics to fulfill EMI shielding attributes. EMI shielding of a composite shielding material depends mainly on the aspect ratio, filler's intrinsic conductivity, dielectric constant, magnetic properties and physical geometry [8,11]. According to the EM wave percolation theory, electrical conductivity of the composite is determined by its ease in forming the conductive network [8,12].…”
Section: Different Types Of Nanocomposites For Emi Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics make PVA an attractive matrix material to host graphene-related fillers. In a recent work [26], very thin (0.3-0.6 mm) graphene nanoribbon/polyvinyl alcohol (GNR/PVA) composite films with different amounts of GNR particles have been developed for shielding EM waves in the X-band. GNR particles were obtained by unzipping multiwall carbon nanotubes [27].…”
Section: Poly Vinyl Alcohol (Pva) Compositesmentioning
confidence: 99%
“…Valentini et al (2015) have presented that the commercial thermoplastic polyurethane filled with exfoliated graphite (EG) composites had a EMI shielding effectiveness of -20 dB with 20 wt.% EG in the frequency of 8.2 to 2.3 GHz. Joshi et al (2013) reported a kind of thin film of graphene nanoribbon-polyvinyl alcohol composite with a high EMI shielding of 60 dB. Thomassin et al (2013) showed different strategies of preparing EMI shielding composites, and the results on EMI shielding effectiveness with various fillers used in the study was ranked as: carbon black < carbon fiber < carbon nanotube < graphene sheet.…”
Section: Introductionmentioning
confidence: 99%